‘Only Brooks of Sheffield’: Conversation, Crossover Writing, and Child and Adult Perspectives in David Copperfield and Its Juvenile Adaptations - Hannah Field (Cahiers Victoriens et Edouardiens)
This article examines the role that conversations between children and adults play in Charles Dickens’s David Copperfield (1850), and late nineteenth- and early twentieth-century adaptations of it for a child audience. First, I show conversation as an important vector in Dickens’s exploration of child and adult knowledge in the original novel. The rules of conversation are suspended in mixed-age companies, as is most powerfully expressed in my titular example: an adult joke turning on the child David’s non-comprehension of a remark by Mr Murdstone. Nonetheless, other conversations show sensitive adults mitigating power differentials between child and adult, and present the child David as unusually perspicacious (in line with his overall characterization). Second, I turn to juvenile adaptations of David Copperfield by writers including Dickens’s granddaughter Mary Angela Dickens. I argue that these works minimize not just the number of conversations in direct speech, but also the process by which David makes conversational inferences; the (now third-person) narrator often fills conversational gaps for the child reader. In the final section, I argue that the relative unimportance of conversation in the adaptations, as opposed to Dickens’s novel, cannot be attributed to concerns with suitability or intelligibility alone. Instead, Dickens’s preoccupation with conversations between adults and children relates to David Copperfield’s original status as a crossover or cross-written text that would have been read by a mixed-age audience. Once this dual address is removed in the adaptations, age-levelled knowledge positions are of much less concern. As such, conversation in David Copperfield metaphorizes the labour (and ethical responsibilities) of the cross-writer.